2022
DOI: 10.1186/s12864-021-08236-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies SNPs for growth performance and serum indicators in Valgus-varus deformity broilers (Gallus gallus) using ddGBS sequencing

Abstract: Background Valgus-varus deformity (VVD) is a lateral or middle deviation of the tibiotarsus or tarsometatarsus, which is associated with compromised growth, worse bone quality and abnormal changes in serum indicators in broilers. To investigate the genetic basis of VVD, a genome wide association study (GWAS) was performed to identify candidate genes and pathways that are responsible for VVD leg disease, serum indicators and growth performance in broilers. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The QTL was also identified in the casecontrol-based GWAS study of the AKP trait mentioned in the background with VVD broilers and sound broilers, the candidate genes located in the QTL were involved in the skeletal development and bone disease. Genetic variation loci of ST3GAL4 gene located in the QTL were closely related to AKP in VVD broilers in their subsequent study which indicated ST3GAL4 plays an important role in serum AKP and the skeletal development [3].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The QTL was also identified in the casecontrol-based GWAS study of the AKP trait mentioned in the background with VVD broilers and sound broilers, the candidate genes located in the QTL were involved in the skeletal development and bone disease. Genetic variation loci of ST3GAL4 gene located in the QTL were closely related to AKP in VVD broilers in their subsequent study which indicated ST3GAL4 plays an important role in serum AKP and the skeletal development [3].…”
Section: Discussionmentioning
confidence: 94%
“…Valgus-varus deformity (VVD) is a leg disease which lateral or middle deviation of the tibiotarsus or tarsometatarsus, accompanied by abnormal changes in serum AKP levels. Case-control (VVD broilers-sound broilers)based GWAS identified 43 SNPs located on Chr24 (0.22 Mb − 1.79 Mb) that were significantly associated with AKP [3]. In the chicken F2 resource population, the direct relationships between AKP levels and candidate genes and corresponding QTLs have not been reported at present.…”
Section: Introductionmentioning
confidence: 99%
“…SAMSN1 ( SAM domain, SH3 domain and nuclear localization signals 1 ) is involved in immune responses as well as reproductive and growth processes ( Zhao et al, 2018 ), potentially reflecting the impact of commercial selection practices. HYLS1 ( Hydrolethalus syndrome 1 ) plays a crucial role in cilia formation and stability; it has been identified as a susceptible gene for Valgus-varus deformity (VVD) and is linked to leg integrity ( Guo et al, 2022 ). ROBO3 ( Roundabout guidance receptor 3 ) is implicated in follicle development in hens ( Qin et al, 2015 ).…”
Section: Disscussionmentioning
confidence: 99%
“…In rainbow trout, quantitative trait loci (QTLs) associated with bodyweight gain were detected using genome-wide association (GWA) analysis, and some genes involved in bodyweight gain were enriched in the cell cycle [23]. In broilers (Gallus gallus), researchers discovered that genes involved in the p53-signaling pathway are associated with the growth performance [24]. These genetic differences may be associated with the differences in body size between the brown-marbled grouper and giant grouper.…”
Section: Analysis Of Genetic Differentiation Between the Brown-marble...mentioning
confidence: 99%